Implementation of E-Monitoring Development and Sales Reports As A Support For Digitalization Of Pt. Amelia Putratama Mandiri's Business Processes - Lailatur Rahmi; Robinson Robinson; Ade Sukma Wati (Bulletin of Network Engineer and Informatics, 2026)
Digitalization has become a strategic necessity for improving company efficiency and competitiveness. PT. Amelia Putratama Mandiri, a cement company, faces crucial challenges such as delayed sales reporting, limited real-time operational monitoring, and a high reliance on manual processes. These challenges pose a risk of information delays and recording errors, which impact business decision-making. This research aims to develop and implement an integrated e-monitoring and sales reporting system to support the digitalization of the company's business processes. This system is designed to improve transparency, speed data access, and reporting accuracy, while also facilitating real-time monitoring of operational and sales activities. The development method used is Agile Development, which emphasizes an iterative and collaborative approach between the development team and users. Development is carried out through several sprint stages, starting from needs identification, interface design, system development, and testing and implementation. This approach allows the system to be flexibly developed according to field needs and continuous user input. The implementation results show that the developed e-monitoring and sales reporting system successfully integrated sales and monitoring processes into a single web-based platform. User testing indicated that the system improved reporting accuracy, accelerated information access, and enhanced operational monitoring efficiency at PT. Amelia Putratama Mandiri.